ON THE ISSUES OF MANAGERIAL PROBLEMS AND DEFICIENCIES IN EVALUATION OF THE EFFICIENCY OF EXECUTIVE BODIES (World Bulletin of Management and Law, 2023)
The main focus of this article is to highlight some of the problems and shortcomings in evaluating the effectiveness of the executive branch on the basis of criteria. The article examines and analyzes the views of scientists and experts who have conducted research on this topic. Based on the results of the study, suggestions and recommendations were developed.